The Role of Kyai in Implementing Discipline Values to the Students at the Pesantren of Darul Arqam in Garut, West Java, Indonesia - Sulaeman, Asep (ASPENSI in Bandung, Indonesia, 2016)
ABSTRACT: Education held in the community includes Islamic educational institutions, that have existed since the early development of Islam in Indonesia and plays a very important role of the formation of national identity and community. This system is called âpesantrenâ (Islamic boarding school). The research is to reveal and analyse in descriptive method about the role of âkyaiâ, or the religious scholar and leader, in implementing the discipline values to the students at the âpeantrenâ of Darul Arqam in Garut, West Java, Indonesia. The theory being used in the analysis is regarding the value meaning and essence, value education essence and goals, the essence of discipline value and the meaning of the âkyaiâ, students, and value education in the âpesantrenâ. Qualitative approach is used as being more suitable than others, and the data gathering is using the following techniques: observation, interview, and textual study. The research objects are the school activities, and the role of the âkyaiâ in implementing discipline among the students. The research shows that by combining traditional and modern education, this Islamic boarding school is able to encourage the students to more discipline in doing compulasory prayers together, doing dawn prayer, and guidance-seeking prayer. The âkyaiâ is able to focus on educate and implement the âtauhidâ (the devine oneness) through tolerance, respecting the elders and guiding the youngers, and loving and devoting the Allah as Lord and His Messanger, Prophet Muhammad.KEY WORDS: Kyai and students, discipline, value education, prayers, and Islamic boarding school.About the Author: Dr. Asep Sulaeman is a Senior Lecturer at the Department of Islamic Civilization History, Faculty of Adab and Humanities UIN (Universitas Islam Negeri or State Islamic University) SGD (Sunan Gunung Djati) Bandung, Jalan A.H. Nasution No.105 Cipadung, Bandung 40614, West Java, Indonesia. Corresponding author is: asepsulaiman99@yahoo.comHow to cite this article? Sulaeman, Asep. (2016). âThe Role of Kyai in Implementing Discipline Values to the Students at the Pesantren of Darul Arqam in Garut, West Java, Indonesiaâ in TAWARIKH: International Journal for Historical Studies, Vol.7(2) April, pp.255-262. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Chronicle of the article: Accepted (January 15, 2016); Revised (March 11, 2016); and Published (April 28, 2016).